(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2012)
A study titled ‘A comparative evaluation of computed tomography (CT) scan findings and autopsy findings in fatal head injury cases’ was carried out in the Department of Forensic Medicine, M.S. Ramaiah Medical College, Bangalore, from October 2009 to March 2011 over a period of 18 months to correlate autopsy findings with CT scan findings in fatal head injury cases. All fatal cases of head injury subjected for post-mortem examination, where ante-mortem CT scan reports were available, were taken up for study. Post-mortem examination of each case was carried out and various types of head injuries were recorded and photographed and the respective CT scan reports were collected. Further, a comparative evaluation of post-mortem findings with that of the CT scan reports was analysed. Of the 270 cases of head injury, 44 (16 %) were hospitalised and a CT scan-head was done. In 37 cases (84%), skull fractures were observed at autopsy, whereas in only 20 cases (45%) the same was commented upon in the CT scan. Basal fractures were more under reported than the vault in the CT scan. Most common type of fractures missed in the CT scan was solitary fissured fracture followed by comminuted fracture. Fractures involving middle cranial fossa were missed more often than other fossae in CT scan. Among intracranial haemorrhages, subarachnoid haemorrhage was missed more frequently than others.